Analysis of Factors Influencing Female Infertility - Indarwati, Ika; Hastuti, Uki Retno Budi; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2017)
Background: Female infertility is one of important public health problems worldwide. According to the World Health Organization, the incidence of infertile cases is increasing each year. Likewise, according to the Central Bureau of Statistics, infertile incidence in Indonesia has been increasing. Dr. Moewardi Hospital Surakarta is one of the hospitals in Central Java Province with increasing number of infertile patients visits. This study aimed to analyze risk factors influencing female infertility.Subjects and Method: This was an analytic observational study with case control design. The study was conducted at Sekar Clinic Dr. Moewardi Hospital, Surakarta from February to March, 2017. A sample of 105 fertile women, consisting of 35 infertile women and 70 fertile women, were selected for this study. The dependent variable was infertility. The independent variables were age, maternal employment status, level of stress, body mass index, abnormal reproductive organ. The data were collected by medical record and questionnaires. The data were analyzed by logistic regression.Results: Female infertility was affected by aged Ã¢â°Â¥35 years old (OR= 4.45; CI 95%= 1.27 to 15.54; p=0.019), career women (OR=3.91; CI 95%= 1.14 to 13.38; p=0.043), high level of stress (OR=3.89; CI 95%=1.04 to 14.46; p=0.046), body mass index(OR=4.37; CI 95%= 1.03 to 18.61; p<0.001), abnormal reproductive organ (OR=11.67; CI 95%= 2.80 to 48.54; p=0.030).Conclusion: female infertility is affected by aged Ã¢â°Â¥35 years old, carrer women, high level of stress, body mass index, and abnormal reproductive organ. Keywords: female infertility, age, level of stress, employment status, body mass index.Correspondence:ÃÂ Ika Indarwati. Masters Programin Public Heath, Sebelas Maret University, Surakarta.ÃÂ Email: ikaindarwaty@gmail.com. Mobile: +6285736222215.Journal of Maternal and Child Health (2017), 2(2): 150-161https://doi.org/10.26911/thejmch.2017.02.02.06